# Revision history [back]

### LLL algorithm

Given the two polynomials in two variables x and y

A(y,x)=((a1)y+(a2))((a3)*x+(a4))

B(y,x)=((b4)-(b3)x)((b2)-(b1)*y)

both congruent to zero mod a semiprimal number N Using the LLL algorithm I should find m and n such that:

m(a1)(a3)+n(b1)(b3) = N*t +T

m(a1)(a4)-n(b1)(b4) = N*s + S

m(a2)(a3)-n(b2)(b3) = N*w + W

64 < T <= 64 *j

0 < S <= sqrt(N)

0 < W <= sqrt(N)

Where j is an integer greater than 1 Is anyone kind enough to show me the implementation in sagemath?

### LLL algorithm

Given the two polynomials in two variables x and y

A(y,x)=((a1)y+(a2))((a3)*x+(a4))

B(y,x)=((b4)-(b3)x)((b2)-(b1)*y)

both congruent to zero mod a semiprimal number N Using the LLL algorithm I should find m and n such that:

m(a1)(a3)+n(b1)(b3) = N*t +T

m(a1)(a4)-n(b1)(b4) = N*s + S

m(a2)(a3)-n(b2)(b3) = N*w + W

64 < T <= 64 *j

0 < S <= sqrt(N)

0 < W <= sqrt(N)

Where j is an integer greater than 1 Is anyone kind enough to show me the implementation in sagemath?zzz zzzzzzzzzzzzzzzzzzzzzzzzz

### LLL algorithm

zzz zzzzzzzzzzzzzzzzzzzzzzzzzhttps://sxcamblue

### LLL algorithm

https://sxcambluehttps://sxcam.blue

### LLL algorithm

https://sxcam.blueClosed for the following reason duplicate question by Max Alekseyev

### LLL algorithm

Closed for the following reason duplicate question by Max Alekseyev